Communicative interventions for collective action in the management of potato late blight: evidence from a framed field game experiment in Ethiopia - Damtew, Elias; Leeuwis, Cees; Struik, Paul C.; Cecchi, F.; Mierlo, B. van; Lie, R.; Lemaga, B.; Cieslik, K. (Springer, 2021)
Potato late blight remains a threat to food security and livelihood of millions of people in Ethiopia. Despite a rapid dispersal of the disease pathogen and farmers’ interdependency in managing it, the literature on agricultural extension and communication tends to frame the disease and its management as a problem of the individual farmer. This study appreciates late blight as a collective action problem whose management requires a corresponding re-configuration in information sharing and communicative practices. We employ a framed field game experiment with a mixed quantitative and qualitative method to explore how and to what extent different types and combinations of communicative interventions affect collective action in the management of the disease among farmers in Ethiopia. Interestingly, our quantitative findings revealed that the provision of technical information about interdependency involved in the management of the disease and social monitoring information about the management practices of other farmers negatively affected collective action. However, collective action performance significantly improved when farmers were given the opportunity to interactively communicate about their management strategies. Further qualitative investigation sheds light on how farmers used and made sense of the different communicative interventions to inform and adjust their individual decisions, coordinate collective strategies, pressure free-riders, and develop a shared identity. It is concluded that interventions that mainly promote the provision of technical and social information can be counterproductive in managing collective action problems such as late blight unless it is complemented with interactive communication and deliberation processes.